Interrogations in Philippine cultural history : the Ateneo de Manila lectures - Mojares, Resil B. (Quezon City, Philippines : Ateneo De Manila University Press, 2017)
Thes articles interrogate diverse issues in the Philippine cultural history : the place of Nick Joaquin in the nation's historiography ' the debate on the class position of Andres Bonifacio and the revolutionary outbreak of 1986 ; Filipino-Spanish interactions in the world of print ; the social history of religious devotions ; the state of regional literary studies and the case of Filipino crime fiction ; and Philippine electoral politics as seen in the cracked mirror of Pascual Racuyal's career. The book ends with the author's reflections on the past four decades of Philippine cultural studies.
Introduction -- Dicourses of the devil's advocate Nick Joaquin as historian -- Andres Bonifacio and the problem of class -- In the colonial world of print -- The Aparicion of the holy child toward a history of a cebuano devotion -- An Immodest proposal for literary studies -- Is there a Philippine Noir? -- The fantistical career of Pascual Racuyal -- Marking a turn : thoughts on a generation of Philippine scholarship.
Includes bibliographical references and index.
Keywords: PHILIPPINE -- HISTORY